Shared liability to pain, common mental disorders, and long-term work disability differs among women and men. Issue 5 (May 2020) - Narusyte, Jurgita; Ropponen, Annina; Mittendorfer-Rutz, Ellenor; Svedberg, Pia
Abstract : Abstract: Knowledge of factors involved in the associations between pain, common mental disorders, and future work incapacity is still scarce. The aim of this study was to examine the overlap between genetic and environmental factors contributing to depression/anxiety, pain, and future long-term sickness absence (SA) and disability pension (DP) among women and men. The study sample included 47, 995 twins born in Sweden 1935 to 1985. Information on self-reported depression/anxiety and back, neck, and shoulder pain was obtained from surveys conducted 1998 to 2002 and 2004 to 2005. Data on long-term SA (>365 days) and DP due to mental and/or musculoskeletal disorders until 2013 were obtained from the National Social Insurance Agency. Shared genetic and environmental influences on depression/anxiety, pain, and SA/DP were estimated by applying structural equation modeling. The prevalence of depression/anxiety was 27% and 14% among women and men, for pain 24% and 19%, and for SA/DP due to mental and musculoskeletal diagnoses 7% and 4%, respectively. Multivariate biometric analyses revealed different patterns of covariation between the 3 phenotypes among women and men. For women, a latent-shared liability to all 3 phenotypes could be identified, mainly attributable to genetic factors (66%). For men, no shared underlying liability was observed. The variation in SA/DP was explained by genetic factors in common with depression/anxiety by 27% and in common with pain by 9%. Common mental disorders, pain, and SA/DP tend to covariate in different ways among women and men. The results may have clinical implications as strategies preventing SA/DP may be different among women and men. Abstract : Supplemental Digital Content is Available in the Text.Etiology of covariation between common mental disorders, pain locations, and work disability tend to differ among women and men raising awareness for sex-specific pathways to work disability.